Evaluasi Efektivitas Mindfulness Therapy terhadap Smoking Cessation: Studi Meta-Analysis - Eka, Grace; Yudiarso, Ananta (Jurnal Ilmu Perilaku, 2023)
The prevalence of smoking which continues to increase into a problem that to this day has not found a concrete solution certainly requires various tactical and dynamic measures, one of which is through therapeutic mindfulness. This research aims to test the effectiveness of mindfulness therapy against smoking cessation in various groups such as adult men, adolescents, and women. This study used a meta-analysis method that used 12 experimental journals on mindfulness therapy and smoking cessation on an international scale published in English, with a total of 1,017 project participants consisting of 498 experimental subjects and 519 control subjects. Result analysis showed an I2 number of 95.29% which was categorized as random effects due to the heterogeneity of the respondent population in the research that became the references. Hedges analysis g is -0.17 which means mindfulness therapy has little effect on the effectiveness of smoking cessation. Results of the analysis also obtained a signification score of egger's regression at 0.895 which is greater than 0.001 (0.001 < 0.895) which concluded no indication of publication bias. The results of this study concluded that mindfulness therapy had a small effect on smoking cessation. This finding is based on smoking cessation status which is more nicotine addiction and not something that can be assessed cognitively, so additional treatment is needed to make the impact significant. Keywords: Meta-Analysis, Mindfulness Therapy, Smoking Cessation